РОЗВИТОК ТВОРЧИХ ЗДІБНОСТЕЙ СТУДЕНТІВ ЧЕРЕЗ ІМІТАЦІЙНО-ІГРОВИЙ ПІДХІД ДО ОРГАНІЗАЦІЇ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2001)
The ways of development creative faculty of the students are examined in this article. The examples of the business-like l>lays that were suspended in the articles, are used in process of the training psycho-pedagogic discipline.